Dandy-Walker Phenotype with Brainstem Involvement: 2 Distinct Subgroups with Different Prognosis - Alves, C.A.P.F.; Sidpra, J.; Manteghinejad, A.; Sudhakar, S.; Massey, F.V.; Aldinger, K.A.; Haldipur, P.; Lucato, L.T.; Ferraciolli, S.F.; Teixeira, S.R.; Öztekin, Ö.; Bhattacharya, D.; et al. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Although cardinal imaging features for the diagnostic criteria of the Dandy-Walker phenotype have been recently defined, there is a large range of unreported malformations among these patients. The brainstem, in particular, deserves careful attention because malformations in this region have potentially important implications for clinical outcomes. In this article, we offer detailed information on the association of brainstem dysgenesis in a large, multicentric cohort of patients with the Dandy-Walker phenotype, defining different subtypes of involvement and their potential clinical impact.MATERIALS AND METHODS: In this established multicenter cohort of 329 patients with the Dandy-Walker phenotype, we include and retrospectively review the MR imaging studies and clinical records of 73 subjects with additional brainstem malformations. Detailed evaluation of the different patterns of brainstem involvement and their potential clinical implications, along with comparisons between posterior fossa measurements for the diagnosis of the Dandy-Walker phenotype, was performed among the different subgroups of patients with brainstem involvement.RESULTS: There were 2 major forms of brainstem involvement in patients with Dandy-Walker phenotype including the following: 1) the mild form with anteroposterior disproportions of the brainstem structures “only” (57/73; 78%), most frequently with pontine hypoplasia (44/57; 77%), and 2) the severe form with patients with tegmental dysplasia with folding, bumps, and/or clefts (16/73; 22%). Patients with severe forms of brainstem malformation had significantly increased rates of massive ventriculomegaly, additional malformations involving the corpus callosum and gray matter, and interhemispheric cysts. Clinically, patients with the severe form had significantly increased rates of bulbar dysfunction, seizures, and mortality.CONCLUSIONS: Additional brainstem malformations in patients with the Dandy-Walker phenotype can be divided into 2 major subgroups: mild and severe. The severe form, though less prevalent, has characteristic imaging features, including tegmental folding, bumps, and clefts, and is directly associated with a more severe clinical presentation and increased mortality.DWDandy-Walker phenotype